Phosphotyrosine prodrugs: design, synthesis and anti-STAT3 activity of ISS-610 aryloxy triester phosphoramidate prodrugs12. Issue 2 (19th November 2018) - Miccoli, Ageo; Dhiani, Binar A.; Mehellou, Youcef
Abstract : The application of the aryloxy triester phosphoramidate prodrug technology to ISS-610-Met improves its ability to inhibit STAT3 in cells. Abstract : Unmasked phohate groups of phosphotyrosine-containing molecules carry two negative charges at physiological pH, which compromise their (passive) cellular uptake. Also, these phosphate groups are often cleaved off by phosphatases. Together, these ultimately limit the pharmacological efficacy of the phosphotyrosine-containing compounds. To address these drawbacks, we herein present the application of the aryloxy triester phosphoramidate prodrug technology, a monophosphate prodrug technology, to the phosphotyrosine-containing compound ISS-610-Met, an analogue of the anticancer STAT3 dimerization inhibitor ISS-610. Our data shows that the generated ISS-610-Met prodrugs exhibited enhanced pharmacological activity and inhibition of STAT3 downstream signaling compared to the parent compound ISS-610-Met and the known STAT3 dimerization inhibitor ISS-610. These encouraging results provide a compelling proof of concept for the potential of the aryloxy triester phosphoramidate prodrug technology in the discovery of novel therapeutics that contain phosphotyrosine and its phospho mimics.